Adaptation of OSIA for grades five and six science classes - Cabato, Ma. Sonia (1973)
The adaptation of OSIA for grades 5-6 science classes in public schools and giving a qualitative and quantitative description of the sample classes were the main purposes of this paper. The conceptual framework of OSIA as a category system were retained on the whole; the definitions of some of its main categories were amplified to include certain behaviors in the classes observed. The findings showed that science teaching and learning behaviors in the sample classes were primarily on the factual level.